1997
DOI: 10.1053/jhep.1997.v26.ajhep0260521
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus: Epidemiology and transmission

Abstract: come apparent because of improved diagnostic techniques Hepatitis C Virus: Epidemiology and physicians' awareness to the possibility of therapeutic intervention. This short review will focus on selected aspects and Transmission of the epidemiology and modes of transmission of HCV. MODES OF TRANSMISSIONTOBIAS HEINTGES AND JACK R. WANDS HCV is generally transmitted by the parenteral route. Well known and common modes of transmission involve transfuHepatitis C virus (HCV) is an RNA virus with a genomic size of 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 9 publications
1
68
0
Order By: Relevance
“…4,6,[10][11][12][13] For example, 34% in USA, although the prevalence of HCV positivity in the general population is similar to Brazil nowadays. [14][15][16] This study infers that the prevalence found is higher than we had expected. Among the 31 positive or indeterminate EIA patients studied by PCR for HCV, 80.6% had viremia, showing a good correlation between EIA and PCR in that population.…”
Section: Discussionmentioning
confidence: 66%
“…4,6,[10][11][12][13] For example, 34% in USA, although the prevalence of HCV positivity in the general population is similar to Brazil nowadays. [14][15][16] This study infers that the prevalence found is higher than we had expected. Among the 31 positive or indeterminate EIA patients studied by PCR for HCV, 80.6% had viremia, showing a good correlation between EIA and PCR in that population.…”
Section: Discussionmentioning
confidence: 66%
“…HCV infection has been found worldwide. Infectivity rates very widely between 0.3% and 14.5% [Heintges and Wands, 1997]. There is a relatively low prevalence of HCV antibodies (anti-HCV) in blood donors derived from the Unite States and Northern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…These observations are in accordance with sparse reports in the literature that pointed at a more frequent distribution of hepatitis C among former athletes (ParanĂĄ et al 1999, Souto et al 2003. In an attempt to explain this finding, a hypothesis was formulated: that the use of injectable vitamin complexes and stimulants -a practice reported as common by individuals engaged in sporting activities some decades ago -could be accountable for the dissemination of the hepatitis C virus (HCV), since the use of contaminated syringes and needles is one of the main known means of transmission of this agent (Heintges & Wands 1997, Shepard et al 2005.…”
Section: Subjetcs Materials and Methodsmentioning
confidence: 99%